2017
DOI: 10.1128/jvi.01955-16
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Anti-HIV gp160 Monoclonal Antibodies That Make Effective Immunotoxins

Abstract: The envelope (Env) glycoprotein of HIV is the only intact viral protein expressed on the surface of both virions and infected cells. Env is the target of neutralizing antibodies (Abs) and has been the subject of intense study in efforts to produce HIV vaccines. Therapeutic anti-Env Abs can also exert antiviral effects via Fcmediated effector mechanisms or as cytotoxic immunoconjugates, such as immunotoxins (ITs). In the course of screening monoclonal antibodies (MAbs) for their ability to deliver cytotoxic age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 75 publications
(140 reference statements)
2
34
0
1
Order By: Relevance
“…Others propose targeting the CD4-binding site (CD4bs) with either MAbs or sCD4 itself (1, 5-7, 9-11, 13). In a companion publication, we again confirmed the efficacy of MAb 7B2 plus sCD4 in killing infected cells and cells stably expressing transfected Env compared to that of highly potent broadly neutralizing MAbs, which killed only cells stably expressing Env and not infected cells (19). We also demonstrated that size limited the ability of ITs targeted against the CD4bs to kill HIV-infected cells.…”
Section: Importancesupporting
confidence: 61%
See 4 more Smart Citations
“…Others propose targeting the CD4-binding site (CD4bs) with either MAbs or sCD4 itself (1, 5-7, 9-11, 13). In a companion publication, we again confirmed the efficacy of MAb 7B2 plus sCD4 in killing infected cells and cells stably expressing transfected Env compared to that of highly potent broadly neutralizing MAbs, which killed only cells stably expressing Env and not infected cells (19). We also demonstrated that size limited the ability of ITs targeted against the CD4bs to kill HIV-infected cells.…”
Section: Importancesupporting
confidence: 61%
“…We found that scFv and other monomeric constructs targeted to the CD4bs functioned well in vitro as ITs, whereas the same V regions in the context of intact Ig were 10 to 100 times less cytotoxic to infected cells (19). In contrast, intact IgG MAbs against the V3 loop of gp120 (MAb 924) and to the gp41 helix-loop region (MAb 7B2) were highly lethal to H9/NL4-3 cells.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations